2022
DOI: 10.3389/fphys.2022.936768
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways and Key Genes Associated With Breast Width and Protein Content in White Striping and Wooden Breast Chicken Pectoral Muscle

Abstract: Growth-related abnormalities affecting modern chickens, known as White Striping (WS) and Wooden Breast (WB), have been deeply investigated in the last decade. Nevertheless, their precise etiology remains unclear. The present study aimed at providing new insights into the molecular mechanisms involved in their onset by identifying clusters of co-expressed genes (i.e., modules) and key loci associated with phenotypes highly related to the occurrence of these muscular disorders. The data obtained by a Weighted Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 133 publications
0
8
0
Order By: Relevance
“…Consequently, researchers have explored genes associated with crude protein content in chicken meat to enhance its protein levels. Leveraging advancements in genomics and bioinformatics, researchers have identified candidate genes linked to crude protein synthesis and metabolism in chicken meat [ 32 , 33 ]. Bordini et al [ 32 ] suggested that breast muscle width and total crude protein concentration can indicate enhanced breast yield and reduced aberrant composition in contemporary broilers.…”
Section: Genetic Factors Influencing Meat Quality Traits In Chickenmentioning
confidence: 99%
“…Consequently, researchers have explored genes associated with crude protein content in chicken meat to enhance its protein levels. Leveraging advancements in genomics and bioinformatics, researchers have identified candidate genes linked to crude protein synthesis and metabolism in chicken meat [ 32 , 33 ]. Bordini et al [ 32 ] suggested that breast muscle width and total crude protein concentration can indicate enhanced breast yield and reduced aberrant composition in contemporary broilers.…”
Section: Genetic Factors Influencing Meat Quality Traits In Chickenmentioning
confidence: 99%
“…To understand the etiology, genetic susceptibility, gene and protein expression, and biochemical pathways associated with breast myopathies, including WS and WB meat, researchers have extensively used genomics ( Alnahhas et al, 2016 ; Pampouille et al, 2018 ), transcriptomics ( Mutryn et al, 2015 ; Marchesi et al, 2019 ; Maharjan et al, 2021 ), proteomics ( Kuttappan et al, 2017 ; Cai et al, 2018 ; Zhang et al, 2020a ; Zhang et al, 2020b ), metabolomics ( Abasht et al, 2016 ; Boerboom et al, 2018 ; Consolo et al, 2020 ), and other methodologies ( Abasht et al, 2021 ; Bordini et al, 2022 ; Bordini et al, 2021 ; Kong et al, 2021 ). Transcriptomics with WS meat identified differentially expressed genes associated with hypoxia, cell death, angiogenesis, immune system, and striated muscle contraction ( Marchesi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the occurrence of myopathies were found among fast-growing commercial lines [ 20 , 21 ]. Several authors have reported that high-breast-yielding broilers are more affected by myopathies than standard broiler lines [ 7 , 10 , 18 , 19 , 22 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analyses of the pectoralis major muscle (PMM) have provided the identification of the messenger RNA (mRNA) expression profile in broilers affected by myopathies [ 25 30 ]. These functional studies have pointed out several candidate genes for the development of these disorders.…”
Section: Introductionmentioning
confidence: 99%